1989
DOI: 10.1093/rheumatology/28.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Jamaican Patients With Systemic Lupus Erythematosus

Abstract: A retrospective study of all patients with systemic lupus erythematosus (SLE) who died at the University Hospital of the West Indies over a 14-year period is presented. The major cause of death was infection followed by renal failure. Gram-negative organisms were the major microbiological agents causing infections. Side-effects of therapy were common, in particular bone marrow depression and haemorrhage related to anticoagulants. It appears that controlling severe lupus activity without increasing the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This is in concordance with data from other centers. Table 7 summarizes the survival experience of other lupus cohorts(3, 5, 7–12, 14, 16, 19, 22, 24–26, 29, 32, 35, 38, 41, 42, 57, 64–70). Although our 5‐year survival rate is lower than the one described in primarily Caucasian cohorts (Europe, Canada), it is the same as or better than the survival rates for contemporary US cohorts that have a significant representation of African Americans, and it is much higher than the survival rates for cohorts from developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with data from other centers. Table 7 summarizes the survival experience of other lupus cohorts(3, 5, 7–12, 14, 16, 19, 22, 24–26, 29, 32, 35, 38, 41, 42, 57, 64–70). Although our 5‐year survival rate is lower than the one described in primarily Caucasian cohorts (Europe, Canada), it is the same as or better than the survival rates for contemporary US cohorts that have a significant representation of African Americans, and it is much higher than the survival rates for cohorts from developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…S I E in African Caribbeans. Data concerning SLE in the West Indies (40)(41)(42)(43)(44)(45)(46) are limited. Wilson and Hughes (45) showed the relatively high prevalence of SLE in hospitalized patients in Jamaica.…”
Section: Sle In Africansmentioning
confidence: 99%
“…Important differences were detected in clinical and immunogenetic variables that could help identify associations with clinical manifestations, disease activity, and physician's global scores. The epidemiology of SLE has been evaluated mainly in North America [2][3][4][5][6][7][8][9][10][11]21,27,29,48,[54][55][56]64,76,77,81,84 and in some European countries 17,19,20,[38][39][40]42,46 , but little information is available from Latin America 1,16,22,23,26,36,37,41,47,49,51,52,65,79 . For obvious reasons, the Latin American studies make few comparisons between ethnic groups, although some have shown a poor prognosis and a high prevalence of infections in African-Latin American (ALA) SLE patients, both of which may relate to socioeconomic variables.…”
Section: Introductionmentioning
confidence: 99%